Sociodemographic and clinical profile of chronic and aggressive periodontitis patients attending IIUM Dental Clinic: a retrospective analysis - Fazid, Nurul Farahin; So'odi, Siti Mahirah; Yaacob, Munirah; Husain, Juzaily; Muhammad Ali, Suhaila (2019)
Introduction and aim: Review of literature showed that qualitative differences between chronic and aggressive periodontitis related to the ethnic and societal factors. This study was aimed to compare the socio-demographic and clinical profile in patients diagnosed with chronic (CP) and aggressive periodontitis (AP) that attending IIUM Dental Clinic and identifies the risk factors related to the disease. Materials and methods: This retrospective study includes the periodontitis cases of the year 2014 to May 2018. The sample included 251 CP, and 19 AP cases. The data was extracted from patients’ case records systematically using data extraction forms. Data analysis was using a Pearson chi-square test and Man Whitney U test. Results: The mean age of AP cases was 38.8 (±8.82) years, and CP was 49.8 (±11.3) (p<0.001). Female gender was significantly found higher in AP as compared to CP (45% vs. 68.4%). The AP cases had showed significant familial tendencies relatively to the CP group (p<0.001). Both groups reported more than half brushing teeth 2 to 3 times per day. About half of AP cases were a student, whereas more than half of CP cases were employed (P<0.001). CP cases significantly appeared with more inadequate oral hygiene and associated with risk factors such as diabetes mellitus (p<0.01). However no significant association with smoking was identified. Differences between the two groups for clinical profiles were statistically insignificant except for full mouth plaque score and number of tooth loss. Conclusion: This study has demonstrated the relative difference in CP and AG for age group, familial tendencies, and lifestyle factors. Despite the significant difference in the identified risk indicators, they did not reflect any considerable influence on the severity of periodontitis. It may be related to a smaller group of AP cases, and the influences of other factors such as host immune and microbial interplay the clinical presentation and progression of the disease.